(untitled) (Research, Society and Development, 2021)
Objective: to investigate the orientation of conducts related to mental health in the context of primary and secondary health care Methodology: Scope Review that seeks to identify the types of evidence available in a given field by analyzing knowledge gaps, clarifying the main concepts and definitions in the literature Results: 10 articles were selected for analysis and elaboration of the synthesis matrix. Results and Discussion: The results were structured in 4 elementary topics according to the data collected, which involve: (1) mental health care; (2) conduct in the technological context; (3) conduct in the face-to-face context; and (4) mental health guidance. Conclusion: Attitudes involving ethics, compassion, moral values and support for both the patient and the professional health team are fundamental.